Fungi and cercozoa regulate methane-associated prokaryotes in wetland methane emissions - Wang, Linlin; Zhao, Mingliang; Du, Xiongfeng; Feng, Kai; Gu, Songsong; Zhou, Yuqi; Yang, Xingsheng; Zhang, Zhaojing; Wang, Yingcheng; Zhang, Zheng; Zhang, Qi; Xie, Baohua; et al. (Frontiers in Microbiology, 2023)
Wetlands are natural sources of methane (CH4) emissions, providing the largest contribution to the atmospheric CH4 pool. Changes in the ecohydrological environment of coastal salt marshes, especially the surface inundation level, cause instability in the CH4 emission levels of coastal ecosystems. Although soil methane-associated microorganisms play key roles in both CH4 generation and metabolism, how other microorganisms regulate methane emission and their responses to inundation has not been investigated. Here, we studied the responses of prokaryotic, fungal and cercozoan communities following five years of inundation treatments in a wetland experimental site. The degree of inundation significantly altered the CH4 emissions, and the abundance of the pmoA gene for methanotrophs shifted more significantly than the mcrA gene for methanogens, and they both showed significant positive correlations to methane flux. Additionally, we found inundation significantly altered the diversity of the prokaryotic and fungal communities, as well as the composition of key species in interactions within prokaryotic, fungal, and cercozoan communities. Mantel tests indicated that the structure of the three communities showed significant correlations to methane emissions (P<0.05), suggesting that all three microbial communities directly or indirectly contributed to the methane emissions of this ecosystem. Correspondingly, the interdomain networks among microbial communities revealed that methane-associated prokaryotic and cercozoan OTUs were all keystone taxa. Methane-associated OTUs were more likely to interact in pairs and correlated negatively with the fungal and cercozoan communities. In addition, the modules significantly positively correlated with methane flux were affected by environmental stress (i.e., pH) and soil nutrients (i.e., total nitrogen, total phosphorus and organic matter), suggesting that these factors tend to positively regulate methane flux by regulating microbial relationships under inundation. Our findings demonstrated that the inundation altered microbial communities in coastal wetlands, and the fungal and cercozoan communities played vital roles in regulating methane emission through microbial interactions with the methane-associated community.